Veiksmažodio šaknies trinarės inicialės ypatumai - Kruopienė, Irena (Kalbotyra, 2005)
The investigation of 1,085 verbal roots showed that the distribution of initial combinations according to their productivity in Lithuanian supported J. Greenberg’s conclusion that more complex consonant combinations occured less frequently than simple ones. The research results of both Lithuanian and Latvian three-member clusters showed that the inventory and productivity of such clusters were rather poor. It was common for Lithuanian verbs to have seven, for Lithuanian nominals five, and Latvian nominals three consonant combinations. Somewhat more frequent were clusters spr, skr, skl- while all others were realized in roots of the verb only sporadically. Nominal three-member initial clusters in Latvian are slightly more productive.According to its frequency in texts, the cluster spr noticeably stood out. Other three-member clusters were used far more seldom. The frequency of verbs with three-member consonant groups was also unequal. The most frequent appeared to be sprę́sti, spréndžia, spréndė ‘to solve’ although there were such combinations, which occurred in the texts very seldom or were never used at all. Hence a much smaller number of verbs were used in the present-day language than there are entries of verbs in the dictionary.